The Role of Supportive Leader, Work Engagement, and Self-Efficacy in Employees' Innovative Behavior: Empirical Study on a National Independent Company - Nindyati, Ayu Dwi (ANIMA Indonesian Psychological Journal, 2012)
Global competitions of the business world today not only make employers think about the advances in technology and additional capital. The quality of human resources was also the focus of study to prepare human resources to compete. One important aspect of this competition is innovation, which is in the individual level known as innovative behavior. The topic of this study is the effect of supportive leader and self-efficacy to employee innovative behavior with work engagement as mediator. Participants/respondents (N = 99) were employees of a national private company. Data analysis was conducted based on the stages of mediation assumption testing of Baron and Kenny (1986) with regression analysis (both simple and multiple regressions). Result showed that work engagement significantly functioned as mediator variable on effect of self-efficacy to innovative behavior. But work engagement is not significant as a mediator variable on effect of supportive leader to innovative behavior. Persaingan global dunia usaha saat ini tidak hanya membuat para pengusaha berpikir tentang kemajuan teknologi dan penambahan modal usaha. Kualitas sumber daya manusia (SDM) juga menjadi focus kajian untuk menyiapkan SDM yang dapat berkompetisi. Salah satu aspek yang penting dalam kompetisi ini adalah innovasi, yang dalam level individual dikenal dengan perilaku inovatif. Penelitian ini mengaji pengaruh supportive leader dan self-efficacy terhadap perilaku inovatif karyawan dengan dimediasi oleh work engagement. Penelitian ini dilakukan terhadap 99 responden yaitu karyawan perusahaan swasta nasional di kota X. Penelitian ini dianalisis dengan menggunakan tahapan pengujian asumsi mediasi dari Baron dan Kenny (1986) yang melibatkan teknik analisis regresi (baik sederhana maupun multi-regresi). Hasil penelitian menyebutkan bahwa work engagement terbukti mampu berperan sebagai mediator pada pengaruh self-efficacy terhadap perilaku innovatif karyawan, namun tidak berfungsi sebagai mediator pada pengaruh supportive leader terhadap perilaku inovatif karyawan.